Effect of Nandrolone Decanoate on Skeletal Muscle Repair - Piovesan, R. F.; Fernandes, K.P. S.; Alves, A. N.; Teixeira, V. P.; Silva Junior, J. A.; Martins, M. D.; Bussadori, S. K.; Albertini, R.; Mesquita-Ferrari, R. A. (International Journal of Sports Medicine, 2013)
This study analyzed the effect of nandrolone decanoate (ND) on muscle repair and the expression of myogenic regulatory factors following cryoinjury in rat skeletal muscle. Adult male Wistar rats were randomly divided into 4 groups: control group, sham group, cryoinjured group treated with ND and non-injured group treated with ND. Treatment consisted of subcutaneous injections of ND (5 mg/kg) twice a week. After sacrifice, the tibialis anterior muscle was removed for the isolation of total RNA and analysis of myogenic regulatory factors using real-time PCR as well as morphological analysis using the hematoxylin-eosin assay. There was a significant increase in MyoD mRNA after 7 days and in myogenin mRNA after 21 days in the cryoinjured ND group in comparison to other groups in the same period. The morphological analysis revealed no edema or myonecrosis after 7 days as well as no edema or inflammatory infiltrate after 14 days in the cryoinjured ND group. In conclusion the anabolic steroid nandrolone decanoate can modulate the muscle repair process in rats following cryoinjury by influencing the expression of regulatory myogenic factors and phases of muscle repair.
Keywords: muscle injury; cryoinjury; nandrolone decanoate; MyoD; myogenin